Understanding dalit assertion for land rights as an outcome of socio-economic dynamics in Punjab - Lal, Sewa (Man & Development)
The present paper is an analysis of socio economic changes occurring among the dalits of Punjab however, Dalits are struggling on every socio-economic parameter in the process of development. Still, within the dalits, three has been a rapid rate of development, which led to the emergence of an active intellectual class among them. After the chievemtn of balad kalan,l the recent assertions and clash for securing the rights bnala districts of Punjab under the leadership of two origination the zameeen Prapati Sanghrsh committee (ZPSC) and the Krantikari Pendu Mazdoor union 9KMPU), there has emerged a strategic response of Dalit intellect calls along with urge for murals respect and equal opportunities in every aspect to human life. - Reproduced
Keywords: Dalits, Activism, Agitation, Clash, Development